2014
DOI: 10.1016/j.jamcollsurg.2014.01.057
|View full text |Cite
|
Sign up to set email alerts
|

Surgeon Volume and Elective Resection for Colon Cancer: An Analysis of Outcomes and Use of Laparoscopy

Abstract: BACKGROUND Surgeon volume may be an important predictor of quality and cost outcomes. We evaluated the association between surgeon volume and quality and cost of surgical care in patients with colon cancer. STUDY DESIGN We performed a retrospective study of patients who underwent resection for colon cancer, using data from the University HealthSystem Consortium from 2008 to 2011. Outcomes evaluated included use of laparoscopy, ICU admission, postoperative complications, length of stay, and total direct hospi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
29
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(30 citation statements)
references
References 24 publications
0
29
0
1
Order By: Relevance
“…22 We also found that as surgeon caseload decreased, so did the odds of receiving laparoscopic resection. Less than 5% of patients in our study had surgery performed by surgeons with annual caseloads of 30+ (based on the study population) whereas 43% had surgeons with annual caseloads of less than 10.…”
Section: Discussionmentioning
confidence: 61%
See 1 more Smart Citation
“…22 We also found that as surgeon caseload decreased, so did the odds of receiving laparoscopic resection. Less than 5% of patients in our study had surgery performed by surgeons with annual caseloads of 30+ (based on the study population) whereas 43% had surgeons with annual caseloads of less than 10.…”
Section: Discussionmentioning
confidence: 61%
“…16 Previous studies have shown extensive variability in laparoscopic surgery utilization based on characteristics of patients [e.g., age, gender, race/ethnicity, socioeconomic status (SES), payer/insurance type, disease stage, comorbidity], hospitals (e.g., size/volume, teaching hospital status, urban/rural, geographic region) 3,5,8,1721 and surgeon caseload. 22 To our knowledge, no studies have examined small area variability (e.g., at the county level) in the use of laparoscopic surgery in the US. Moreover, no studies concurrently examined variation across patients, hospitals, and geography.…”
Section: Introductionmentioning
confidence: 99%
“…The statement deduced from our literature review, although extreme and by our count too low, should be discussed and be either confirmed or rejected by an expert committee with the aim to define profound minimum volumes. We also outlined the known threats of centralization, namely unjustified exclusion of high-quality surgeons, leaving excluded surgeons and hospitals [11,13,30], leaving emergency surgery to low-volume surgeons (LVS) or LVH (excluded from selective surgery), implicating worse experience with surgical oncological treatment of CRC offered to the patients with the highest risk [11], the realistic danger of overload concerning HV [11], and, last but not least, the observation that patients who traveled farther for their care had worse outcomes than expected. This statement, cited in the review by Etzioni et al [23] and called 'reverse distance bias' in their discussion, may be relevant for the US situation but not necessarily for Western European countries, e.g.…”
Section: Discussionmentioning
confidence: 99%
“…However, two of these papers also come to the conclusion that the impact of volume on outcome 'may be' positive when correlated to HVH [11,12] (these authors found a positive correlation for HVS). The estimation 'maybe' is made by one group only for the category HVS [13], but not for HVH. These authors reject a correlation between volume and quality for HVH.…”
Section: Colon Cancermentioning
confidence: 99%
“…This may partially explain why, despite 25 years of evidence that a minimally invasive approach to right colon cancer achieves significant clinical and oncological benefits compared with open surgery, the application of laparoscopic colorectal surgery is still limited both in Europe and in the USA , and this is particularly true when performing an intracorporeal anastomosis. Most centres and surgeons in the UK and Europe still feel uncomfortable when attempting an ICA because of the fear of improper closure of the enterotomy and subsequent increased risk of a postoperative leak.…”
mentioning
confidence: 98%